(untitled) (Research, Society and Development, 2021)
Due to the increase in the prevalence of obesity in the world and consequent submission to gastric bypass surgery, there is evidence of the need to carry out constant nutritional support for two patients after bariatric surgery so that the expected results of the surgical procedure are obtained. This integrative literature review study aimed to present nutritional needs and point out the bariatric plate model as an auxiliary strategy for the adequate intake of macronutrients and micronutrients for patients undergoing gastric bypass surgery. Meanwhile, it is necessary to carry out studies that validate the use of this instrument. Finally, regular multidisciplinary accompaniment is essential to avoid or develop deficiencies of two main nutrients observed over the course of the review.